Japanese physicians' attitudes towards enteral nutrition treatment for pediatric patients with Crohn's disease: a questionnaire survey - Takashi Ishige (Intestinal Research, 2017)
Background/Aims: Enteral nutrition (EN) is recommended for the treatment of pediatric Crohn's disease (CD) in Japan. However, the indications and treatment protocols for EN vary among hospitals. In the present study, we aimed to determine how EN was administered to pediatric patients and whether physicians followed treatment guidelines in their practices.Methods: Two types of questionnaires were administered to 32 physicians who were involved in the treatment of pediatric CD. The consensus questionnaire evaluated the physicians' attitudes towards EN, whereas the efficacy questionnaire collected data on patients with CD, aged <17 years, who had undergone induction therapy between 2006 and 2011.Results: A total of 23 physicians responded to the questionnaires. The results of the consensus questionnaire indicated that 82% and 59% of study participants recommended EN treatment for all newly diagnosed pediatric patients with CD and all relapsed patients, respectively. Exclusive EN (EEN) and elemental formula were recommended by 84% and 85% of physicians, respectively. The efficacy questionnaire revealed that 57 of the 58 patients received EN. Elemental formula was used in 39 of 40 patients who were treated with EEN. Of these 40 patients, 27 were treated with EEN alone; of these, 22 (81%) achieved remission without any other treatment. The mean duration of EEN was 15.9 days.Conclusions: EN is widely recommended by physicians treating pediatric CD in Japan. In contrast to Western countries, clinicians used elemental formula more often and with a shorter EEN treatment duration.